1993
DOI: 10.1111/j.1365-2133.1993.tb11850.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin for the treatment of acne vulgaris: which factors may predict the need for more than one course?

Abstract: We investigated 299 patients treated 5-10 years ago with isotretinoin, and followed them for 5 years post-treatment. Of the 299 patients 22.7% required repeat courses of treatment; 17% had two courses, 5% had three courses and 1% had 4-5 courses. Response to further treatment was predictably successful, was not associated with any additional adverse reactions, and produced no persistent side-effects. Factors contributing to the need for further courses of treatment included lower dose regimens (0.1 and 0.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 10 publications
1
63
0
5
Order By: Relevance
“…The greater the severity of acne at the onset of therapy and the longer the length of time that the acne has been present also correlates with a greater risk for relapse. 77,78 Truncal acne appears to be more resistant than facial. Those patients that do relapse most commonly do so in the first year and rarely after the third year post treatment.…”
Section: Long-term Side Effects/efficacymentioning
confidence: 99%
“…The greater the severity of acne at the onset of therapy and the longer the length of time that the acne has been present also correlates with a greater risk for relapse. 77,78 Truncal acne appears to be more resistant than facial. Those patients that do relapse most commonly do so in the first year and rarely after the third year post treatment.…”
Section: Long-term Side Effects/efficacymentioning
confidence: 99%
“…Patients followed over 5 years after completing their initial course of OI required an additional course in 22.7 %, two additional courses in 17 %, and three additional courses in 5 % of cases [21]. A retrospective review of a large managedcare practice database reported that 61 % of AV patients treated with a course of OI later underwent retreatment for AV, with 22.9 % undergoing at least one additional course of OI [22].…”
Section: Historic Data On Need For Retreatment After Oral Isotretinoimentioning
confidence: 99%
“…The subset of patients who needed at least one additional course of OI usually completed this within 2 to 3 years, of their initial course [1, 4, 12••, 13-17••, [18][19][20][21][22][23][24][25]. Given the same duration of OI therapy which was usually 16 to 20 weeks, a consistent trend for recurrence of AV has been observed in several studies, with a lower daily dose (0.1 -0.2 mg/kg/day) associated with a higher recurrence rate and often an earlier onset of recurrent AV as compared to higher daily doses (0.5-mg/kg/day; 1 mg/ kg/day) [12••, 13-17••, [18][19][20][21][22][23][24][25]. The culmination of data analysis supports that a course of OI achieves a total dose of 120 -50 mg/kg to reduce the potential for recurrence of AV (Table 1) [17••, 18-22].…”
Section: Outcomes From Data Analyses On Need For Retreatment After Ormentioning
confidence: 99%
“…Принято при легкой степени течения акне ограничиваться применением топических препаратов в сочетании со средствами ухода, однако среднетяжелые Одним из наиболее востребованных ретиноидов на сегодняшний день является изотретиноин. Известно, что клинический ответ на терапию акне изотретиноином сле-дует ожидать на 16-20 неделе приема препарата при суточной дозе от 0,1 мг/кг/день до 1 мг/кг/день [8,9]. Наилучший терапевтический эффект изотретиноина достигается при кумулятивной дозе препарата от 120 до 150 мг/кг [10].…”
unclassified